2016
DOI: 10.1080/03630242.2016.1243604
|View full text |Cite
|
Sign up to set email alerts
|

The prevalence and risk factors for osteoporosis among 18- to 49-year-old Turkish women

Abstract: The aim of this study was to determine the prevalence of osteoporosis and associated risk factors in Turkish women aged 18-49 years. A population-based, cross-sectional study was conducted between January and April 2014. The sample (n = 1,792) was comprised of women aged 18-49 years, who resided in Cubuk, Ankara, Turkey, and were selected by simple random sampling. The data were collected in face-to-face interviews using an Individual Information Form and an Osteoporosis Risk Estimation Scale. Bone mineral den… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 34 publications
1
6
0
Order By: Relevance
“…Consanguinity was present in 48% of the patients in our study. This rate proves to be more than double the rate of consanguinity in Turkey (20%) 20 . Furthermore, a sibling of one of our patients died with similar symptoms.…”
Section: Discussionsupporting
confidence: 52%
“…Consanguinity was present in 48% of the patients in our study. This rate proves to be more than double the rate of consanguinity in Turkey (20%) 20 . Furthermore, a sibling of one of our patients died with similar symptoms.…”
Section: Discussionsupporting
confidence: 52%
“…This rate proves to be more than the double the rate of consanguinity in Turkey (20%). 19 Furthermore, a sibling one of our patient's died with similar symptoms. Our result, in line with those of previous studies, indicates that genetics might play a role in the underlying mechanisms of IPH.…”
Section: Discussionmentioning
confidence: 51%
“…A study in Turkey showed that women between the ages of 18–49 who smoke, have fair skin, or have a family history of osteoporosis are at higher risk for osteoporosis [ 7 ]. The clinical symptoms of osteoporosis in old age include decreased body height, dowager’s hump or kyphosis, bone fracture and respiratory impairment [ 8 ].…”
Section: Introductionmentioning
confidence: 99%